Childhood-Onset Schizophrenia: A Systematic Overview of Its Genetic Heterogeneity From Classical Studies to the Genomic Era - Fernandez, Arnaud; Drozd, Malgorzata Marta; Thümmler, Susanne; Dor, Emmanuelle; Capovilla, Maria; Askenazy, Florence; Bardoni, Barbara (Frontiers in Genetics, 2019)
Childhood-onset schizophrenia (COS), a very rare and severe chronic psychiatric condition, is defined by an onset of positive symptoms (delusions, hallucinations, disorganized speech or behavior) before the age of 13. COS is associated with other neurodevelopmental disorders such as Autism Spectrum Disorder (ASD) and Attention Deficit and Hyperactivity Disorder (ADHD). Copy Number Variations (CNVs) represent well documented neurodevelopmental disorder risk factors and, recently, de novo Single Nucleotide Variations (SNVs) in genes involved in brain development have also been implicated in the complex genetic architecture of COS. Here, we aim to review the genetic changes (CNVs and SNVs) reported for COS, going from previous studies to the whole genome sequencing era. We carried out a systematic review search in PubMed using the keywords "childhood(early)-onset schizophrenia(psychosis)” and “genetic(s) or gene(s) or genomic(s)” without language and date limitations. The main inclusion criteria are COS (onset before 13 years old) and all changes/variations at the DNA level (CNVs or SNVs). 36 studies out of 205 met the inclusion criteria. Cytogenetic abnormalities (n=72, including 66 CNVs) were identified in 16 autosomes and two sex chromosomes (X, Y), some with a higher frequency and clinical significance than others (e.g., DEL2p16.3, 3q29, 15q13.3, 22q11.21; 2p25.3, 3p25.3 and DUP16p11.2). 31 SNVs in genes principally involved in brain development and/or function have been found in 12 autosomes and one sex chromosome (X). We also describe five SNVs in X-linked genes inherited from a healthy mother, arguing for the X-linked inheritance hypothesis. Moreover, ATP1A3 (19q13.2) is the only gene carrying more than one SNV in more than one patient, making it a candidate for COS. Mutations were distributed in various chromosomes illustrating the genetic heterogeneity of COS. More than 90% of CNVs involved in COS are also involved in ASD, supporting the idea that there may be genetic overlap between these disorders. Different mutations associated with COS are probably still unknown, and pathogenesis might also be explained by the association of different genetic variations (two or more CNVs or CNVs and SNVs) as well as association with early acquired brain lesions such as infection, hypoxia or early childhood trauma.